(untitled) (Al-Academy, 2023)
Modern digital technologies have affected the means of communication in terms of structure, function and methods of dealing with them, and the communication process has changed, becoming bilateral, reciprocal and interactive, after it was one-way and limited in circulation and the roles changed, so the receiver became the sender and reversed is correct, and the culture of the active user and the participant spread, and the communication process became continuous.The international information network has provided new electronic channels in the media and communication that are not known and opened a new era for these means, which led to a trend towards digital media in an unprecedented way.The new communication platforms are the result of modern digital technologies, represented by Facebook, WhatsApp, Telegram, Twitter, blogs and other electronic platforms, and they have an important communication role in societies, therefore societies have become open after they were closed to themselves, and this in turn affected the process of communication, contact and the formation of public opinion, whether was it negatively or positively.The innovations that were reinforced by digital technologies and modern technology, began to lead us towards a new arrangement of the communication system, where the traditional communication process was transformed and the information transmission process became involving new digital communicative interaction processes, previously uncharacteristic, in this regard, the researcher noticed the importance of this topic in highlight on these drastic transformations in the process of communication and digital contact, and the research problem was identified. Through the following questions: 1. What is digital technology, the new structure of modern means of communication.2. What are the changes and the new environment brought by digital technology and its role in the process of digital communication and contact.